Sandstone-hosted uranium mineral prospectivity mapping based on ResNet50 self-distillation - Weijian Zheng; Jianfeng He; Weidong Li; Fei Xia; Fengjun Nie; Zizheng Yu; Caijun Gong; Guoyun Zhong; Fan Diao (Computational Geosciences, 2026)

Effects of microbial-derived artificial humic acid on soil organic carbon stability and microbial community fractions under straw return conditions - Jiaxun Liang; Huaiyuan Teng; Le Liu; Fengjun Yang; Liqin Zhao; Bowen Fan; Jingyi Lan (Applied Soil Ecology, 2026)

Corrigendum to ’Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism’[Volume 159, January 2026, Pages 166-177] - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

The Effect of Humic Acid From Different Raw Materials on Soil Physical and Chemical Properties and Tomato Seedling Growth - Lanjing Long; Liqin Zhao; Xiangjun Chen; Zhicheng Liu; Xue Chen; Bowen Fan; Fengjun Yang (Journal of Soil Science and Plant Nutrition, 2026)

Rapamycin enhances rice resistance to Rhizoctonia solani by reconstructing endophytic microhabitat and ROS homeostasis - Siyu Guo; Jingjing Peng; Changyu Zhu; Bowen Fan; Qin Yao; Fengjun Yang; Changjiang Zhao (Physiological and Molecular Plant Pathology, 2026)

Biodegradable polybutylene adipate terephthalate packaging with dual-functionality: Synergistic effects of curcumin coating and laser micro-perforation on sweet cherry preservation - Zhijie Zuo; Xiao Chen; Ming Li; Xinhua Zhang; Binshan Mu; Yijing Li; Zhanjun Guo; Changfeng Zhang; Xinguang Fan; Fujun Li; Fengjun Guo (Food Packaging and Shelf Life, 2026)

Flocoumafen exposure induces skeletal developmental toxicity and neurotoxicity in zebrafish (Danio rerio) - Tianyi Chen; Fengjun Fan; An Cheng; Yumei Xia; Haoze Chen; Jiakai Fang; Yangyu Chen; Tianjia Li; Anli Wang; Binjie Wang; Weixuan Yao; Yuanzhao Wu (Toxicology Letters, 2026)

Visible light photocatalytic enhanced heterogeneous cobalt catalyzed peroxymonosulfate synergistic process to degradation atrazine: Efficiency, influencing factors, by-products removal and mechanism - Qingkong Chen; Jieyu Xia; Fengjun Liu; Jianping Fan; Peng Yan; Mika Sillanpää (Journal of Environmental Sciences, 2026)

Preparation of mesoporous polydopamine/thyme essential oil/fish scale gelatin photothermal antibacterial film and its application on cherry tomato preservation - Yunfeng Yang; Quanwen Liu; Peng Yang; Xiulian Li; Xiangquan Zeng; Fengjun Guo; Xinguang Fan (Food Chemistry, 2026)

Responsive packaging that adapted to and regulated physiological metabolic of fruits and vegetables: Mechanism, application and prospects - Chunjun Chen; Yibing Ding; Yucong Feng; Xiulian Li; Chanchan Sun; Fengjun Guo; Xiangquan Zeng; Hansheng Gong; Xinguang Fan (Trends in Food Science & Technology, 2025)

ADB-FUBINACA-induced developmental toxicity, neurotoxicity, and cardiotoxicity in embryonic zebrafish (Danio rerio) - Yuanzhao Wu; Fengjun Fan; Lu Zhou; Yihang Shen; Anli Wang; Yazhou Qin; Jiye Wang; Weixuan Yao (Environmental Research, 2025)

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

The preparation of fish scale gelatin-polydopamine photothermal sterilization film and its application for storage of cherry tomato - Yunfeng Yang; Xiulian Li; Ting Zhang; Xiangquan Zeng; Fengjun Guo; Quanwen Liu; Xinguang Fan; Da-Peng Yang (Food Packaging and Shelf Life, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Biochar application can enhance phosphorus solubilization by strengthening redox properties of humic reducing microorganisms during composting - Bowen Fan; Changjiang Zhao; Liqin Zhao; Mengmeng Wang; Ning Sun; Zoutong Li; Fengjun Yang (Bioresource Technology, 2024)

Rice bran is a key structure affecting high nutrition and low toxicity of indica hybrid rice (Oryza sativa L.) - Yu Fan; Yujie Yuan; Zhiyou Gong; Yajun Wang; Xiufeng Mei; Fengjun Yan; Tao Wang; Fei Deng; Yong Chen; Xiaolong Lei; Jianfeng Hu; Youfeng Tao; et al. (Journal of Cereal Science, 2023)

Human Cytomegalovirus IE2 Disrupts Neural Progenitor Development and Induces Microcephaly in Transgenic Mouse - Delei Niu; Xianjuan Zhang; Shuyun Zhang; Tianyu Fan; Xiaoqiong Zhou; Hui Wang; Xueming Zhang; Fulong Nan; Shasha Jiang; Fengjun Liu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2023)
Human cytomegalovirus (HCMV) is a significant contributor to congenital birth defects. Limited by the lack of animal models, the pathogenesis of neurological damage in vivo caused by HCMV infection and the role of individual viral genes remain to be elucidated. Immediate early (IE2) protein may play a function in neurodevelopmental problems caused by HCMV infection. Here, this study intended to investigate IE2’s long-term effects on development of the brain in IE2-expressing transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) aimed to observe the phenotype of postnatal mice. The expression of IE2 in transgenic mice was confirmed by PCR and Western blot technology. We collected mouse brain tissue at 2, 4, 6, 8, and 10 days postpartum to analyze the developmental process of neural stem cells by immunofluorescence. We discovered that transgenic mice (Rosa26-LSL-IE2 +/− , Camk2α-Cre) can reliably produce IE2 in the brain at various postpartum phases. Furthermore, we also observed the symptoms of microcephaly in postnatal transgenic mice, and IE2 can damage the amount of neural stem cells, prevent them from proliferating and differentiating, and activate microglia and astrocytes, creating an unbalanced environment in the brain’s neurons. In conclusion, we demonstrate that long-term expression of HCMV-IE2 can cause microcephaly through molecular mechanisms affecting the differentiation and development of neural stem cells in vivo. This work establishes a theoretical and experimental foundation for elucidating the molecular mechanism of fetal microcephaly brought by HCMV infection in throughout the period of neural development of pregnancy. Graphical Abstract

Extended lag phase indicates the dormancy of biphenyl degrading Rhodococcus biphenylivorans TG9 under heat stress - Jiahui Fan; Jinsong Feng; Dongdong Xu; Xinyi Li; Fengjun Xu; Haoming Li; Chaofeng Shen (Environmental Pollution, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

The Role of F-Fluorodeoxyglucose (FDG) Positron Emission Tomography–Computed Tomography (PET/CT) in the Screening of Cervical Cancer: A Literature Review - Fengjun Guo; Ruiqi Yang; Jingyan Tian; Limei Fan (Cell Biochemistry and Biophysics, 2014)